Integrating green recruitment and digital technology: Indirect influence on employee performance through digital competencies - Samodra, Vegalyra Novantini; Iristian, Jovi; Sidjabat, Sonya; Husainah, Nazifah; Saptaria, Lina (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to analyze the direct and indirect relationships between Green Recruitment, Digital Technology, Digital Competence, and Employee Performance at PT Adhi Karya (Persero) Tbk. Specifically, it examines how Digital Competence mediates the influence of Green Recruitment and Digital Technology on employee performance in the construction sector. Methodology: A quantitative research approach was employed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Data were collected from 194 employees through purposive sampling, and the questionnaire used a five-point Likert scale. The analysis included validity, reliability, and hypothesis testing using SmartPLS 4.0.. Results: The findings reveal that both Green Recruitment (? = 0.225, p < 0.01) and Digital Technology (? = 0.411, p < 0.001) significantly enhance Digital Competence. In turn, Green Recruitment (? = 0.203), Digital Technology (? = 0.253), and Digital Competence (? = 0.437) significantly improve Employee Performance. Moreover, Digital Competence mediates the indirect influence of Green Recruitment (? = 0.098, p < 0.01) and Digital Technology (? = 0.180, p < 0.001) on performance. Conclusions: Integrating sustainable recruitment practices and digital transformation strategies strengthens employee competencies and organizational productivity in construction companies. Limitations: The study focuses on one SOE, limiting generalizability, and does not include moderating variables such as digital leadership or organizational culture. Contribution: This study extends Green HRM and digital transformation theories by providing empirical evidence that Digital Competence serves as a critical bridge between sustainability-oriented HR policies and enhanced employee performance in the digital era.